Perawatan Internal Bleaching Untuk Estetik Gigi Pasca Perawatan Endodotik - Diana Soesilo (Denta Journal Kedokteran Gigi, 2016)
Background: In general, everyone likes white teeth as a symbol of beauty and health. Discoloration can be caused by extrinsic and intrinsic factors. One of the factors that cause teeth discoloration is due to the trauma that causes the teeth to be non vital. One alternative treatment that becomes an option is internal bleaching. Case: 37-year-old female patient with # 11 and # 21 non vital post-endodontic treatments and color changes to blackish color especially on cervical parts. Case Management: Gutta percha point taking 2-3 mm below orifice using peeso reamer. Application of Glass Ionomer type 3 cement over gutta percha point as base. Etching with 37% phosphoric acid for 20 second was then washed etching and dried with cotton pellet. The bleaching superoxol material (30-35% Hydrogen Peroxide) was appliedto the pulp chamber and then covered with cotton and Glass Ionomer type 2 cement to prevent leakage of bleaching material. Control is done once a week until the appropriate color of the tooth is obtained. Conclusion: Treatment that can be done to restore the color of the original tooth without making an excessive reduction to the dental crown is by internal bleaching.